A randomized controlled trial comparing two ways of providing evidence-based drug information to GPs. (June 2013) - Skoglund, Ingmarie; Björkelund, Cecilia; Petzold, Max; Gunnarsson, Ronny; Möller, Margareta
Abstract Objective. To investigate whether tailored evidence-based drug information (EBDI) to general practitioners (GPs) can change the proportion of ACE inhibitor prescriptions more effectively than EBDI provided as usual three and six months after the intervention. Design. Randomized controlled trial. Setting. GPs in southern Sweden working at primary health care centres (PHCCs) in seven drug and therapeutic committee areas. Intervention. EBDI tailored to motivational interviewing (MI) technique and focused on the benefit aspect was compared with EBDI provided as usual. Subjects. There were 408 GPs in the intervention group and 583 GPs in the control group. Main outcome measures. Change in proportion of ACE inhibitor prescriptions relative to the sum of ACE inhibitors and angiotensin receptor blockers, three and six months after the intervention. Results. The GPs' average proportions of prescribed ACE inhibitors increased in both groups. No statistically significant differences in the change of proportions were found between intervention and control groups. Information was provided to 29% of GPs in both groups. Conclusion. This study could not prove that specially tailored EBDI using MI implements guidelines more effectively than EBDI provided as usual.